Organizational Communication Culture in Village Governments and the Quality of Administrative Services in Sidoarjo District of Indonesia - Ade Putra Satria; Totok Wahyu Abadi; Nur Aini Shofiya Asy'ari; Anurat Anatanatorn (Universitas Darussalam Gontor, 2025)
Organizational communication culture in Indonesia, especially in Sidoarjo, still faces challenges in the form of ineffective interaction between the village government and the community, which results in low understanding and participation of residents in utilizing administrative services. The purpose of this study is to explain the influence of organizational communication culture of village government on the quality of administrative services in the village. This quantitative study uses a simple random sampling technique in data collection. Primary data collected from 106 village government officials in Sidoarjo Regency as respondents were processed and analyzed using multiple linear regression analysis. The results of the analysis show that organizational communication culture has a significant influence of 84.6% on the quality of administrative services, with accountability (66%) and teamwork (46.1%) as the dominant factors that strengthen service quality. In contrast, the variables of community service (-69.2%), openness of communication (-63.5%), and coordination (-65.6%) actually have a negative impact on the quality of administrative services. Based on these findings, the study recommends the need to improve communication culture in village government organizations as a strategic step to improve the quality of administrative services and increase responsiveness to community needs.